EDUCATION IN/IN THE COUNTRYSIDE AND LITERACY IN MULTISERIATED CLASSES (TEL Tempo, Espaço e Linguagem, 2023)
This article brings some reflections on education in/in the countryside and literacy in multigrade classes based on the conceptions and conditions of existence of the peoples that inhabit this space, from the perspective of school work in the recognition and appreciation of children's identity. Its objective is: to understand the process of multigrade education in the countryside with regard to the conceptions and conditions of existence, as well as the teaching and learning process developed in that space. This is an excerpt from the literature review of the Master's dissertation in Education, completed in 2022, by the Graduate Program in Education - PPGed, at the Federal University of Piauí - UFPI.